2001
DOI: 10.1080/20014091111974
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenic Risk of Toluene Diisocyanate and 4,4′-Methylenediphenyl Diisocyanate: Epidemiological and Experimental Evidence

Abstract: Diisocyanates are highly reactive compounds widely used, for example, in the production of polyurethane foams, elastomers, paints, and adhesives. The high chemical reactivity of these compounds is also reflected in their toxicity: diisocyanates are one of the most important causes of occupational asthma but also other adverse effects, such as irritation and toxic reactions, have been described in exposed subjects. One of the open questions is whether occupational isocyanate exposure is a carcinogenic hazard. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 79 publications
2
65
0
Order By: Relevance
“…Although the pathogenesis of diisocyanate-induced asthma is still largely unknown (Baur et al, 1994;Bolognesi et al, 2001), increasing evidence from human and laboratory animal models has indicated that the OA induced by TDI shares several features with allergic asthma (Wisnewski and Redlich, 2001). Indeed intranasal instillation of TDI resulted in systemic T H 2-dominated immune responses characterized by lower T H 1 cytokines (IFNγ ) associated with a rise in T H 2 cytokines (IL-4, IL-5, IL-6, and TNFα).…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathogenesis of diisocyanate-induced asthma is still largely unknown (Baur et al, 1994;Bolognesi et al, 2001), increasing evidence from human and laboratory animal models has indicated that the OA induced by TDI shares several features with allergic asthma (Wisnewski and Redlich, 2001). Indeed intranasal instillation of TDI resulted in systemic T H 2-dominated immune responses characterized by lower T H 1 cytokines (IFNγ ) associated with a rise in T H 2 cytokines (IL-4, IL-5, IL-6, and TNFα).…”
Section: Discussionmentioning
confidence: 99%
“…19 Although this behavior would be beneficial for an adhesive the degradation or hydrolysis of adhesive systems based on aromatic diisocyanates results in formation of aromatic diamines that are known to be carcinogenic. 20 However, we have reported in a previous study that sufficient solidification speed can be achieved even with aliphatic diisocyanates when aqueous solution of chitosan chloride is used instead of pure water. 21 Chitosan chloride contains AOH and ANH 2 groups that enable reaction with isocyanate groups under formation of stable urethane or urea bonds and acceleration of solidification.…”
Section: Introductionmentioning
confidence: 96%
“…Isocyanates are not considered human carcinogens, although TDI is classified as an animal carcinogen and MDI as a suggested animal carcinogen (Rom & Markowitz 2007). Additionally, epidemiologic studies on mainly TDI and MDI foam production workers have not shown a higher prevalence for any cancer (Bolognesi et al 2001).…”
Section: Impact On Human Healthmentioning
confidence: 99%
“…2) and 3) further decomposition of the materials to primary amines, secondary amines, vinyl esters and carbon dioxide. Adapted from Jiao et al (2013) (Jiao et al 2013) No (Nehez et al 1989) No (Nehez et al 1989 Severe (Vernot et al 1977) Severe (Vernot et al 1977) Toluene-2,4-diisocyanate (2,4-TDI) (Bolognesi et al 2001) No (Zocca et al 1990) Yes (Buschmann 1990) Insufficient evidence (Hughes et al 2014) Lungs (Hughes et al 2014) Irreversible decline in pulmonary function (Centers for Disease Cotrol and Prevention 2015e)…”
Section: Impact On Human Healthmentioning
confidence: 99%